Company Response to Job Training Students of Politeknik Negeri Jakarta’s Commercial Administration Department’s Competence - Sinaga, Mawarta Onida; Hartati, Tuti; Widhi, Ni Made; Nailufar, Eva Zulfa; Mustofa, Anwar (International Journal Labs, 2023)
Background: Job Training activities or Field Work Practices (PKL) are one of the requirements that must be carried out by students of the Business Administration Study Program, Department of Commercial Administration, Politeknik Negeri Jakarta. This obligation is carried out by students after they graduate from semester 5. Aim: The purpose of this study is to determine the company's response to the competence of students of the Department of Commercial Administration, Politeknik Negeri Jakarta when implementing PKL and company expectations for the major. Method: The research design used in this study was descriptive qualitative. Data collection was applied retrospectively from the provided. The research was conducted in a company collaborating with the Business Administration Study Program, Department of Commercial Administration, Politeknik Negeri Jakarta and was a place for students to conduct PKL for the period of February to April 2017. The sample was selected using a simple random sampling technique with a minimum number of samples taken from each class of 13 students based on the Slovin formula. Findings: The ability of students to adapt to the environment in a very special category. Student initiative and creativity towards the corporate environment in a very special category. Students communication skills were categorized as very special. Potential student attitudes appear in the very special category. Skills in carrying out tasks include conformity with instructions, quality of work results, punctuality and problem-solving ability are very special categories. The discipline and independence of the community towards the company environment in the category was very special.